Pengembangan LKS Fisika Berbasis Contextual Teaching and Learning Materi Suhu dan Kalor Pada Siswa Kelas XI SMA Negeri 6 Lubuklinggau - Inda Anggun Restu; Wahyu Arini (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to develop physics worksheets based on contextual teaching and learning materials for temperature and heat in class XI students of SMA Negeri 6 Lubuklinggau which aims to find out how to develop and quality valid, practical. The problem in this study is the valid and practical quality of the Physics Worksheet based on Contextual Teaching and Learning of Temperature and Heat. This research method is development (Research and Development) used is 4D (Four D) with 4 stages Define, Design, Develop and Desseminate. The population in this study was class XI IPA 2 with 28 students. The sampling technique used positive sampling using 6 samples. Data collection techniques in this study used interviews, diagnostic test questions, expert validation questionnaires, teacher response questionnaires, student response questionnaires and Physics Worksheets Based on Contextual Teaching and Learning. The results of the validation questionnaire data analysis with 3 validator experts were the results of the validation of the physics lecturer material 42, the results of the validation of the physics teacher material with a score of 46. The results of the validation of the linguists got a score of 18, the results of the validation of the media expert got a score of 34, so the final score obtained after validation of 35 with a very good category, the results of the 6 student response questionnaires obtained a score of 35.83 with the category of strongly agree and the results of the questionnaire response of the teacher and students got a score of 36.2 with the category of strongly agree. The results of competency test scores to support practicality obtained competency test scores obtained on average 76.5% complete reaching ≥ 73.So it can be said that physics worksheets based on Contextual Teaching and Learning Material Temperature and Heat in Class XI Students of SMA Negeri 6 Lubuklinggau are valid. and practical.